2017
DOI: 10.1002/cam4.1030
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted:Effects of miR‐145‐5p throughNRASon the cell proliferation, apoptosis, migration, and invasion in melanoma by inhibitingMAPKandPI3K/AKTpathways

Abstract: We aimed to detect the effects of miR‐145‐5p on the cell proliferation, apoptosis, migration, and invasion in NRAS‐mutant, BRAF‐mutant, and wild‐type melanoma cells, in order to figure out the potential mechanisms and provide a novel therapeutic target of melanoma. RT‐qPCR and western blot were used to detect the expression of miR‐145‐5p and NRAS in melanoma tumor tissues and cells, respectively. Luciferase assay was performed to determine whether miR‐145‐5p directly targeted NRAS. After transfecting miR‐145‐5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 45 publications
5
69
0
Order By: Relevance
“…In the present study, they confirmed that the MAPK signaling pathway in T24 cells were synergistically repressed by the cotreatment with miR‐143/‐145 . Similarly, through targeting NRAS, miR‐145‐5p could suppress cell functions by inhibiting MAPK pathways . These were the same exploration as us that miR‐145‐5p inhibited MYD88 and related proteins in MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, they confirmed that the MAPK signaling pathway in T24 cells were synergistically repressed by the cotreatment with miR‐143/‐145 . Similarly, through targeting NRAS, miR‐145‐5p could suppress cell functions by inhibiting MAPK pathways . These were the same exploration as us that miR‐145‐5p inhibited MYD88 and related proteins in MAPK signaling pathway.…”
Section: Discussionsupporting
confidence: 86%
“…[29][30][31][32] LPS increases the secretion of pro-inflammatory cytokines in fibroblast-like synoviocytes, which leads to the activation of the PI3K/ AKT and MAPK/mTOR pathways, thereby inducing apoptotic and inflammatory injury in these cells. [34][35][36][37] We demonstrated that miR-145 could partially eliminate the LPS-induced activation of PI3K/AKT and MAPK/ mTOR pathways in MH7A cells, implying that the protective activities of miR-145 might be realized by blocking the PI3K/AKT and MAPK/mTOR pathways. Protein expressions of core components of (A), PI3K/AKT, and (B), MAPK pathways were evaluated, after MH7A cells were transfected with miR-145 mimic or mimic-control, and subsequently treated with 5 μg/mL of LPS for 5 hours.…”
Section: Discussionmentioning
confidence: 81%
“…miR‐145‐5p could suppress cell proliferation, invasion, and migration and induce apoptosis of CHL‐1 and VMM917 melanoma cells by inhibiting mitogen‐activated protein kinas (MAPK) and phosphatid‐ylinositol 3 kinase/protein kinae B (P13k/AKT) pathways . It might also function as a cardiac‐protective molecule in myocardial ischemic injury by ameliorating inflammation and apoptosis via negative regulation of CD40 .…”
Section: Discussionmentioning
confidence: 99%